A 3D walking palm-like core–shell CoMoO4@NiCo2S4@nickel foam composite for high-performance supercapacitors. Issue 12 (1st February 2019) - Hussain, Iftikhar; Ali, Awais; Lamiel, Charmaine; Mohamed, Saad Gomaa; Sahoo, Sumanta; Shim, Jae-Jin
Abstract : 3D core–shell binder-free CoMoO4 @NiCo2 S4 @NF with excellent stability and high capacitance was developed as a positive electrode material for supercapacitors. Abstract : Supercapacitors are one of the most promising renewable-energy storage systems. In this study, a three-dimensional walking palm-like core–shell CoMoO4 @NiCo2 S4 @nickel foam (NF) nanostructure was synthesized using a two-step hydrothermal method for high electrochemical performance. The as-prepared composite exhibited a high areal capacitance of 17.0 F cm −2 (2433 F g −1 ) at a current density of 5 mA cm −2 in a three-electrode system. The results revealed outstanding cycling stability of 114% after 10 000 charge–discharge cycles. An aqueous asymmetric supercapacitor device assembled with CoMoO4 @NiCo2 S4 @NF and activated carbon (AC)@NF as the positive and negative electrodes, respectively, showed a high capacitance of 4.19 F cm −2 (182 F g −1 ) and delivered a high energy density of 60.2 W h kg −1 at a power density of 188 W kg −1 and a high power density of 1.5 kW kg −1 at an energy density 29.2 W h kg −1, lighting 22 parallel-connected red light emitting diodes for over 60 s. The synergistic effects of the core–shell CoMoO4 @NiCo2 S4 @NF electrode material highlight the potential of this composite as an effective active material for supercapacitor applications.